OPPORTUNITIES, THREATS AND VARIABILITY OF BUSINESS MODELS OF POLISH BUSINESSES ADAPTING OUTSOURCING – RESEARCH RESULTS - Jakub DRZEWIECKI (Modern Management Review, 2016)
The aim of this article is the presentation of result of an empirical research related to: perception of opportunities and threats among Polish businesses using outsourcing as well as dependency between perception of opportunities and threats and changes made in the business models of the investigated enterprises. The research paper consists of an introduction, a summary and four main sections. The first of the main sections contains the description of the methodology and characterization of the research sample in the cross-section of selected quality features. In the second section, the original concept of the variability of the business models based on the A. Osterwalder’s concept of business models is described. The third part contains the results of the research about the perception of opportunities and threats related to the investigated enterprises. The article is concluded by the presentation of the results concerning the correlation between the changes made in the respective areas of business models of the investigated subjects, the probability of occurrence of the identified opportunities, and threats estimated by them. The results of the research indicate a significance of a business model as a strategic management tool, in particular in strategic change management. The indicated dependencies between the variables included in the research are a premise denoting the possibility to use business model in the context of adaptation of organization to its environment.